Difficulties in Learning English by EFL Students in Turkey - Demet Özmat; Nuray Senemoğlu (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
The purpose of this study is to determine the factors that contribute to English language learning difficulties. Study participants included 2317 secondary and high school students from the state schools of the Ministry of Education in Ankara. Data was derived through the Foreign Language Learning Difficulties Scale (LLDS) developed (2017) by the researches and semi structured interviews. Quantitative data was analyzed through SPSS, a statistical program for social sciences research, and the qualitative data was analyzed through MaxQda 12, software for qualitative and mixed methods research with 70 students in total. The findings of the foreign language learning difficulties scale showed that both 7th and 11th grade students had high levels of difficulties in the foreign language learning process. When the difficulties between the two grades were compared, results showed that 11th grade students had higher levels of language learning difficulties than 7th grade students. Results of semi-structured interviews showed that the most common difficulties experienced by students were insufficient communicative practice in textbooks, insufficient use of visual and audio instruments in the classrooms, insufficient practices of listening and speaking abilities, lack of language learning teaching strategies, low self-confidence, crowded classrooms and disciplinary problems.